2003
DOI: 10.1080/14445921.2003.11104142
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Property Sector and Geographic Diversification in Australian Institutional Property Portfolios

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…This evidence of market segmentation suggests that there are diversification benefits from including LPTs in an investment portfolio, particularly in conditions of increased stockmarket volatility (Newell and Acheampong, 2001). Both diversified and sector-specific strategies are equally effective for LPT portfolio diversification (Newell and Tan, 2003), with LPTs also showing evidence of superior property selection and market timing (Peng, 2004). The establishment of an LPT futures market in August 2002 further enhanced the stature of LPTs, with institutions being able to use LPT futures as an effective risk management tool for hedging their LPT exposure (Newell and Tan, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…This evidence of market segmentation suggests that there are diversification benefits from including LPTs in an investment portfolio, particularly in conditions of increased stockmarket volatility (Newell and Acheampong, 2001). Both diversified and sector-specific strategies are equally effective for LPT portfolio diversification (Newell and Tan, 2003), with LPTs also showing evidence of superior property selection and market timing (Peng, 2004). The establishment of an LPT futures market in August 2002 further enhanced the stature of LPTs, with institutions being able to use LPT futures as an effective risk management tool for hedging their LPT exposure (Newell and Tan, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…They allow liquidity and transparency to property investment (Newell, ; Dolvin and Pyles, ) not generally available to direct property investment. Additionally, the inclusion of REITs in an investment portfolio can act as a defensive stock (Glascock et al ., ; Newell and Tan, ; Newell, ) due to their lower volatility and diversification benefits (Ratcliffe and Dimovski, ). The Australian REIT sector is recognised as a world leader in securitised property (Higgins and Ng, ) and now comprises an important component of the property market (Parker, ).…”
Section: A‐reit Institutional Backgroundmentioning
confidence: 99%
“…The authors found that diversifying investments internationally by sector is a better strategy than other forms of strategies. In a similar vein, Newell and Keng (2003) evaluated the effectiveness of sector versus regional diversification in Australia. Using the Property Council of Australia (PCA) property authors found that both property type and geographic diversification delivered significant diversification benefits [3].…”
Section: Literature Reviewmentioning
confidence: 99%